Effect of hydrofluoric acid concentration and etching time on resin-bond strength to different glass ceramics - Veríssimo, Aretha Heitor; Moura, Dayanne Monielle Duarte; Tribst, João Paulo Mendes [UNESP]; Araújo, Arthur Magno Medeiros de; Leite, Fabíola Pessôa Pereira; Souza, Rodrigo Othávio de Assunção E (FapUNIFESP (SciELO), 2019)
The objective of this study was to evaluate the effect of the hydrofluoridric acid (HF) concentration and time of acid conditioning on bond strength of three glass ceramics to a resin cement. Thus, fifty blocks (10 mm x 5 mm x 2 mm) of each ceramic (LDCAD: IPS e.max CAD; LCAD: IPS Empress CAD and LDHP: IPS e.max Press) were made and embedded in acrylic resin. The surfaces were polished with sandpaper (#600, 800, 1000, and 1200 grits) and blocks were randomly divided into 15 groups (n = 10) according to the following factors: Concentration of HF (10% and 5%), conditioning time (20 s and 60 s) and ceramic (LDCAD, LDHP, and L). After conditioning, silane (Prosil / FGM) was applied and after 2 min, cylinders (Ø = 2 mm; h = 2 mm) of dual resin cement (AllCem / FGM) were made in the center of each block using a Teflon strip as matrix and light cured for 40 s (1,200 mW/cm2). Then, the samples were thermocycled (10,000 cycles, 5/55°C, 30s) and submitted to the shear bond test (50 KgF, 0.5 mm/min). The data (MPa) were analyzed with 3-way ANOVA and Tukey's test (5%). Failure analysis was performed using a stereomicroscope (20x) and a scanning electron microscope (SEM). ANOVA revealed that the concentration factor (p = 0.01) and the interaction acid concentration X ceramic (p = 0.009) had a significant effect, however, the ceramic (p = 0.897) and conditioning time (p = 0.260) factors did not influence the results. The LDHP10%60s (10.98 MPa)aA* group presented significantly higher bond strength than LDHP10%20s (6.57 MPa)bA, LCAD5%20s (6,90 ±3,5)aB and LDHP5%60s (5.66 ± 2,9MPa)aA* groups (Tukey). Failure analysis revealed that 100% of specimens had mixed failure. In conclusion, etching with 5% HF for 20 seconds is recommended for lithium disilicate and leucite-reinforced CAD/CAM ceramics. However, for pressed lithium disilicate ceramic, 10% HF for 60 s showed significantly higher bond strength to resin cement.